Performance of broilers fed graded levels of cassava leaf-meal - AWOJOBI, H A; ADEKUNMISI, A A (The Indian Journal of Animal Sciences, 2014)
A feeding trial was conducted to evaluate the performance of broilers fed graded levels (0,5, 10,15 and 20%) of cassava leaf meal (CLM) in a corn-soybean based diet. The starter and finisher diets were formulated to be isocaloric and isonitrogcnous. The starter diet contained approximately 2825 Keal ME/kg and 21 % CP while the finisher diel contained approximately 2930 Keal ME/kg and 18% CP. Each diet was fed ad lib, to 4 replicates of6 birds per replicate 3 weeks. Results of the experiment showed no significant (P